(untitled) (Acta Scientiarum. Agronomy, 2025)
Root-knot nematodes (RKNs), including Meloidogyne graminicola and M. ottersoni, have recently been identified in Santa Catarina and Paraná in southern Brazil. Therefore, our study aimed to evaluate the host status of nine irrigated rice cultivars and five Oryza accessions inoculated with M. ottersoni and M. graminicola [initial population (IP) = 5,000 specimens] under greenhouse conditions across two experimental periods. We assessed the host status based on the nematode reproduction factor (RF) and the number of nematodes per gram of root. For both nematodes, all the rice cultivars we studied were classified as susceptible, with RF means ranging from 21.80 to 108.92 for M. ottersoni and 2.12 to 177.16 for M. graminicola. Conversely, the Oryza accessions displayed varied phenotypes. For example, O. grandiglumis, O. glaberrima, and O. glumaepatula exhibited moderate to high resistance to M. ottersoni, with RFs ranging from 0.53 to 4.50, while O. latifolia was susceptible. Additionally, O. glumaepatula showed moderate to high resistance levels to M. graminicola (RF = 0.23 – 8.88), whereas O. alta was susceptible, and O. grandiglumis, O. glaberrima, and O. latifolia demonstrated varying levels of resistance. Overall, our findings suggest that the Oryza accessions we studied could be promising sources of resistance for developing new cultivars in the future.